Elit Lokal Madura: Sisi Kehidupan Kaum Blater - Muh. Syamsuddin (Jurnal Lektur Keagamaan, 2015)
This article is summative work of the research result of the life of Blater Community: A study of local elite in Madura. With the use of phenomenological approach, the research highlights some important findings.First, the Blater community of Sampang District is fanatic muslims. The Blater whom are socially categorized as “jagoan” (fighter), who has a particular style of life, imfact, they are able to interact and adapt to their social environment. Second, the sexual life of Blater community is socially built based on the agreement approach among them.